Annexin A5–Functionalized Nanoparticle for Multimodal Imaging of Cell Death - Rui Zhang; Miao Huang; Min Zhou; Xiaoxia Wen; Qian Huang; Chun Li (Molecular Imaging)
Techniques for visualizing cell death can provide noninvasive assessment of both disease states and response to therapeutic intervention. The purpose of this study was to develop and evaluate a multimodal imaging nanoplatform for the detection of cell death. In this study, we evaluated 111 In-labeled annexin A5–conjugated core-cross-linked polymeric micelles (CCPMs) for multimodal imaging of cell death in various disease models. Three different models were conducted, including tumor apoptosis, hepatic apoptosis, and inflammation. Both micro single-photon emission tomography/computed tomography (μSPECT/CT) and fluorescence molecular tomography (FMT) were performed. Biodistribution and immunohistochemistry assays were carried out to validate the selectivity of cell death imaging. In all disease models, cell death was clearly visualized by both μSPECT/CT and FMT. In contrast, there was relatively low signal in the corresponding tissues of control mice. Moreover, the radioactive signal from 111 In-labeled annexin A5–CCPM colocalized with its fluorescence signal, and both signals were confined to regions of dying cells. 111 In-labeled annexin A5–CCPM allows visualization of cell death by both nuclear and optical techniques at the whole-body level as well as at the microscopic level. It has the potential to aid the diagnosis of disease states or tissue responses involving abnormal cell death.